International and European policy on work and retirement: Reinventing critical perspectives on active ageing and mature subjectivity. (January 2013) - Moulaert, Thibauld; Biggs, Simon
In this article, the authors critically examine themes that have become associated with work and retirement in the context of demographic change. Two discourses are looked at in detail, those of 'active' and 'productive' ageing, with a focus upon International and European social policy. Drawing on the work of Foucault and others, the emergence of a dominant discourse and its effects on policy-based understandings of ageing are examined. A new orthodoxy of ageing subjectivity is identified, restricting the social contribution of older adults to work and work-like activities. A subtext refers to the co-option of liberal gerontological priorities into new and socially rigid forms of identity that legitimize particular ways of growing old. The authors conclude that a radical re-positioning, inspired by mature identity, is required to rely less upon economically determined roles and more upon alternative grounding in existential life tasks and experience to give space for a 'mature subjectivity' and a desirable 'mature subject'.